Ab-initio study of LD-HfO2, Al2O3, La2O3 and h-BN for application as dielectrics in MTJ memory device. (February 2021) - Sharma, Bikash; Thapa, Abinash; Sarkar, Arghyadeep
Abstract: Low-dimensional (LD) forms of HfO2, Al2 O3, La2 O3 and h -BN have been used as dielectric layer in the proposed MTJ memory device. Subsequently, DFT and NEGF model based atomistic computation were performed for the device using Quantum ESPRESSO. Self-consistent Field (SCF), Density of State (DOS) and Bandstructure calculations were carried out. The SCF converged uniquely for all LD materials used. Lowest energy was obtained for multilayer LD-La2 O3 at −1760.7200095Ry and HfO2 at −940.365Ry, thus predicting better accuracy in solving Schrödinger equation and wave functions. The DOS plots exhibited the valence band sharp peaks at −4.5eV, −0.5eV, −0.5eV and −4.25eV for multilayer LD-HfO2, Al2 O3, La2 O3 and h -BN respectively. The energy band spacing manifested from DOS plots were found to be better for LD- HfO2, La2 O3 and h -BN. On inspecting the bandstructure plots, higher bandgap was observed for multilayer LD-HfO2 (at 3.8eV), hence depicting it to have a better insulating property. Upon device computation, higher TMR was obtained for HfO2 based MTJ memory device (i.e. 2.5 at 0 V), showcasing better readability of bits. While consistent boundary voltages were obtained from the DTMR calculations for h -BN and HfO2 based devices, concluding them to have better stability of the memory states. The overall results obtained for different performance parameters of the MTJ memory device using LD-HfO2 and h -BN were very impressive. Thus, predicting these materials as highly promising to be used as dielectrics in a MTJ memory device. Highlights: The very study of Magnetic Tunnel Junction (MTJ) memory device is of high interest in the current scenario of the saturation of the existing MOS devices. The study of low-dimensional (LD) forms of materials is another reason of very high interest due to their unique properties. The ab-initio study the low-dimensional forms of HfO2, Al2O3, La2O3 and h-BN has given very interesting results and their applications as dielectrics. The application of the LD forms of the above-mentioned materials as dielectrics in a MTJ memory device shows very promising results and a comparison of these materials have been shown in the work. Overall, the work is unique and the results are promising for further study and application.